Menjawab Kebutuhan Siswa Melalui Layanan Bimbingan dan Konseling: Strategi Profesional Guru BK di Sekolah - Nabila Rezky Palenza; Yarmis Syukur; Taufik Taufik (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
Guidance and Counseling (BK) services have a strategic role in responding to students’ increasingly complex needs, both in academic, personal, social, and career aspects. BK teachers as professionals are required to design and implement appropriate and sustainable service strategies. This article discusses various professional strategies that BK teachers can implement in responding to students’ needs, including through needs assessments, individual and group counseling services, curriculum-based program development, humanistic approaches, and the use of digital technology. The importance of ethics and professionalism in implementing BK services in schools is also emphasized. By implementing the right strategy, BK teachers are able to create an environment that supports optimal student growth. This article also identifies the challenges faced by BK services and solutions that can be implemented to improve the effectiveness of the role of BK teachers in schools.